Extension Of The Periods For Consent To And Payment Of Quota Increase. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2019)
On June 25, 2019, the IMF's Executive Board approved a further six-month extension of the period for members to consent to an increase in their quotas under the Fourteenth General Review of Quotas ('Fourteenth Review') through December 27, 2019. The deadline was due to expire on June 28, 2019. However, Board of Governors Resolution No. 66-2 provides that the Executive Board may extend the period for consent as it may determine. An extension under Resolution No. 66-2 also extends the periods of consent for quota increases under the 2008 Reform of Quota and Voice (Resolution No. 63-2) and the Eleventh General Review of Quotas (Resolution No. 53-2). The Executive Board also approved a further six-month extension of the period for payment of quota increases under the Fourteenth Review, and an extension for the payment of the quota increases under the 2008 Reform, through December 27, 2019.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Board Of Governors Resolution No. 66-2; Payment Of Quota; Payment Period; PP; Quota Payment; Syrian Arab Republic